Factors associated with choice of psychotropic drugs used for intentional drug overdose - Tournier, Marie; Grolleau, Adeline; Cougnard, Audrey; Molimard, Mathieu; Verdoux, Hélène (European archives of psychiatry and clinical neuroscience, 2009)
Introduction Knowledge of the factors influencing the choice of drugs used for intentional drug overdose (IDO) may allow the reduction of IDO lethality. Objectives To assess with which frequency subjects with intentional overdose of psychotropic drugs ingest their own psychotropic drug treatment, and whether prescription of a drug may be a factor influencing the choice of drugs used for the IDO. Methods Demographic characteristics, psychiatric history, and currently prescribed psychotropic drug treatment were collected for all the patients ( n = 1,654) admitted to an emergency department (ED) for IDO with psychotropic drugs (anxiolytics, hypnotics, antidepressants, neuroleptics and mood stabilizers) over a period of 18 months. Drugs ingested for the IDO were compared in subjects who had ingested at least one psychotropic drug that was prescribed for them and subjects who had ingested psychotropic drugs not prescribed for them using multivariate logistic regression. Results Two-thirds of the patients ingested during the IDO at least one of their own prescribed psychotropic drugs. Compared with the subjects who had ingested psychotropic drugs not prescribed for them, they were more likely to have a history of psychiatric hospitalization (OR 4.2; 95%CI 3.1–5.5), of being a psychiatric outpatient (OR 3.9; 95%CI 3.0–5.1), of parasuicide (OR 2.5; 95%CI 1.9–3.3) and a serious IDO (OR 2; 95%CI 1.4–2.9). Independently from age and psychiatric hospitalization history, they ingested during the IDO more often antidepressants (OR 4.4; 95%CI 3.0–6.4), antipsychotics (OR 2.9; 95%CI 1.7–4.8) and mood stabilizers (OR 4.1; 95%CI 1.6–10.7). No association was found with prescription for overdose of hypnotic (OR 1.1; 95%CI 0.8–1.5), anxiolytic (OR 1.2; 95%CI 0.9–1.7) or paracetamol (OR 1.0; 95%CI 0.5–2.1). Conclusion Prescription of the psychotropic drugs plays an important role in the choice of the drugs ingested for the IDO. It might make potentially “dangerous” drugs available for the patient. Physicians have always to balance the benefit of the treatment against the risk of drug overdose.